From ancient Asian relics to contemporaneity: A review of historical and chemical aspects of Cannabis - Marques, Gabriel Vitor de Lima; Oliveira, Renata Barbosa de (European Journal of Chemistry, 2023)
From the Himalayan mountains to the South American coast, Cannabis, a general term for plants of the genus Cannabis, with thousands of years of contact with humankind, shows its versatility as food tools such as hemp, religious and hedonistic input, and other purposes through the millennia, according to the populations in question. In this paper, a review of the context of the use of Cannabis and its place in world history is presented, from ancient Mesopotamian relics, traditional Chinese and Ayurvedic medicines, to the reasoning behind the isolation and structural elucidation of three phytocannabinoids and the spread of Cannabis throughout the world.